Dual Frequency Integrated Antenna (DFIA) with image rejection - Ismail, W. (School of Microelectronic Engineering, 2013)
A new configuration of integrated antenna featuring dual frequency operations and image frequency rejection is implemented. The used of dual frequency for image rejection in one system by using one antenna is a new technique in demodulation. The LNA's, mixers, LO and coupler are integrated to a dual frequency microstrip patch antenna producing a single module of integrated system that can perform for multiband operations.